Struktur Kepribadian Tokoh Iryân dalam Novel al-Rajulu al-Lazî Âmana Karya Najib al-Kailani (Analisis Psikologi Sigmund Freud) - Ali Nur Yasin; Darisy Syafaah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
The purpose of this study is to determine the personality structure of the Iryâ n character in the novel Al-Rojulu Al-Lazî Âmana by using Sigmund Freud's theory. The research method used is descriptive qualitative with analysis content techniques descriptive analysis. The results of this study illustrate that there are many findings about the personality structure of the character Iryâ n in the novel Al-Rojulu Al-Laz î Amana. There are eight forms of Id which are instincts to meet sexual needs and also instincts to gain comfort in life. There are also 6 forms of Ego which are responsible for decision making and reasoning. The superego in Iryân consists of three forms that connect Iryân's reasoning with conscience, morality and religious norms. Overall, the character Iryân fits into the form of Id. Although not all forms of Id that exist in Iryân occur.